Analysis of uncontrollable supply effects on a co-production demand-driven wood remanufacturing mill with alternative processes. Issue 3 (2nd July 2016) - Rafiei, Rezvan; Nourelfath, Mustapha; Gaudreault, Jonathan; De Santa-Eulalia, Luis Antonio; Bouchard, Mathieu
ABSTRACT: This article applies an optimization and simulation framework to identify the impacts of uncontrollable supply in the demand-driven wood remanufacturing industry. In the remanufacturing business, providing supply of raw materials in terms of quality is an uncontrollable process, especially when combined with other industry characteristics such as divergent co-production, alternative processes, make-to-order philosophy and short order cycle times. By considering a set of key performance indicators (KPIs) to measure production plan efficiency, our framework uses a periodic re-planning strategy based on a rolling horizon. Then, the source of lumber is perturbed, leading to different supply scenarios. Simulations are conducted using a mixture experimental design approach to identify the safety threshold of supply changes in the scenarios regarding the selected KPIs. This threshold of all KPIs leads us to an overall optimum region which includes a series of desirable scenarios. The proposed framework allows planner to understand the impact of supply policies to deal with uncertainties.